Think Asean! : - Kotler, Philip (McGraw - Hill, 2007)
Compelling marketing is pertinent marketing. Marketing relevancy takes effort and imagination but the rewards are immense as the companies highlighted in think ASEAN. This book provides valuable insights into how ASEAN and multinational corporations have successfully worked their marketing magic in the region.